2021
DOI: 10.17221/332/2021-pse
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan in modern agriculture production

Abstract: In the perspective of return to nature, using scientific and technical progress for improved living standards, people began to search for solutions to alleviate environmental pollution. Researchers intend to make clean, affordable products that are gentle yet effective. Chitosan derived from the exoskeleton of crustaceans, cuticles of insects, cell walls of fungi, and some algae are renowned for many decades to exhibit biotic properties, especially anti-microbial characteristics. Here we review each ingredient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(21 citation statements)
references
References 131 publications
(119 reference statements)
0
21
0
Order By: Relevance
“…4 A). The MDA contents decreased [ 46 56 ] significantly under normal as well as under stress as a result of priming treatments (Fig. 4 B).…”
Section: Resultsmentioning
confidence: 96%
“…4 A). The MDA contents decreased [ 46 56 ] significantly under normal as well as under stress as a result of priming treatments (Fig. 4 B).…”
Section: Resultsmentioning
confidence: 96%
“…This suggested that the insecticidal efficacy of the CAP was enhanced by chitosan-based encapsulation. Chitosan and its derivatives (i.e., CMCS) could be used in pesticide delivery, copolymeric concentration, and nanomicellar, which could effectively prevent ecological harm, including the photodegradation of the active ingredients [ 51 ]. In addition, chitosan could give the CAP loaded in microcapsules good solubility and permeation into the insect gut, causing a series of adverse reactions, such as delayed growth and development, decreased adult weight and reproduction rate, and even death [ 49 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chitosan, a β 1,4-linked glucosamine polymer, is the deacetylated form of chitin obtained from organisms such as fungi, shrimps, and crab (1) . Chitosan has several applications in biomaterials, pharmaceutical drug delivery systems (2) , medical (3) , textile (4) , agricultural and pesticide applications (5) , preservatives (6) , wastewater purification (7) , and dressing materials for wounds (3) . Chitosan has antibacterial activity; therefore, it is used in making gloves, wound bandages, and sterile textiles (5) .…”
Section: Introductionmentioning
confidence: 99%